Patai's Chemistry of Functional Groups 2014
DOI: 10.1002/9780470682531.pat0869
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom‐substitued Dioxetanes and their Emerging Biomedical Applications

Abstract: Heteroatom‐substituted dioxetanes are one subclass of dioxetanes that have at least one heteroatom (such as O, S, N) at its two carbons of dioxetane structures. These are readily formed from the [2+2] cycloaddition reaction of heteroatom‐substituted alkenes and singlet oxygen ( 1 O 2 ). Due to their unique characteristics, such as chemiluminescence and spontaneous cleavage, heteroatom‐substituted dioxetanes have been used for a number of biomedical applications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…). Reports have described visible or NIR light to disconnect drugs from sensitizer molecules, as a means for simultaneous PDT and delivery of anti‐cancer drugs, such as paclitaxel . Related NIR uncaging and sensitization reactions have also been reported for cyanines and phthalocyanines .…”
Section: Fiber Optics and Handheld Implements In Pdtmentioning
confidence: 99%
“…). Reports have described visible or NIR light to disconnect drugs from sensitizer molecules, as a means for simultaneous PDT and delivery of anti‐cancer drugs, such as paclitaxel . Related NIR uncaging and sensitization reactions have also been reported for cyanines and phthalocyanines .…”
Section: Fiber Optics and Handheld Implements In Pdtmentioning
confidence: 99%
“…We 27,28 and others 2931 have published papers devoted to 1 O 2 -based drug release and a book chapter has also appeared. 32 Singlet oxygen is a potentially therapeutic species and is photogenerated by PAHs, 33,34 chlorins, 35,36 porphyrins and phthalocyanines, and their fluorinated analogs. 3741 In 2011, Röder et al reported the deposition of perfluorinated phthalocyanines on silica gel as a composite material for generating 1 O 2 for sterilization.…”
Section: Introductionmentioning
confidence: 99%
“…Visible light and NIR photocleavage reactions are known and actually represent a burgeoning area of research. , For example, the sensitized generation of 1 O 2 ( 1 Δ g ) has been used with labile ethene linkers for photorelease reactions. We , and others have published papers devoted to 1 O 2 -based drug release, and a book chapter has also appeared . Singlet oxygen is a potentially therapeutic species and is photogenerated by PAHs, , chlorins, , porphyrins and phthalocyanines, and their fluorinated analogues. In 2011, Röder et al reported the deposition of perfluorinated phthalocyanines on silica gel as a composite material for generating 1 O 2 for sterilization .…”
Section: Introductionmentioning
confidence: 99%